Pengaruh Penggunaan AI Song Maker Terhadap Minat Belajar Peserta Didik Pada Pembelajaran Biologi Materi Sistem Reproduksi Kelas XI Fase F - Nailatul Fadilah; Relsas Yogica (LP2M UIN Ambon, 2026)
This study aims to determine the effect of using AI Song Maker as a song-based learning medium on students’ interest in learning about the reproductive system. The method used was a quasi-experiment with a Posttest-Only Control Design, employing random sampling to select two 11th-grade classes at Bukittinggi State High School 2: Class XI F1 as the experimental class and Class XI F3 as the control class. The research instrument consisted of a 18-question student learning interest questionnaire. The results of the study showed that the average posttest score for the experimental class (65.04) was higher than that of the control class (77.08). This proves that the use of AI Song Maker in the learning process has a significant effect on students’ interest in learning, thereby fostering feelings of joy, attention, curiosity, and engagement in the learning process, and is consistent with various learning theories that affirm that song-based media can serve as an effective stimulus in the learning process.